Urban Mobility Plans in Italy - Papa, Enrica; Battarra, Rosaria (TeMA - Journal of Land Use, Mobility and Environment, 2010)
Urban transport plan according to the Italian national Law n.340/ 2000 have the specific aim of improving the traffic situation in the cities. Mobility plans consider all modes of transport planned towards a sustainable urban development. The measures implemented are a mixture of material and immaterial interventions with the aim to reach a better traffic environment with reduced traffic volumes and emissions, increased accessibility and safety and an increased quality of life for all citizens. In Italy, according to the principle that the mobility strategies cannot be separated from the land use planning, many cities are developing innovative Mobility Plans that are integrated with urban planning actions. In order to underline these best practices, a comparative study is proposed between five different urban areas in the central and northern Italy. Most innovative plans have within their strategies the following points: – Promote integrated policies to deal with the complexity of urban transport systems, governance issues and the necessary coherence between different policies, for example between urban mobility and cohesion policy, environment policy or health policy. – Help to green urban transport by introducing new, clean vehicle technologies and alternative fuels and promoting smart charging to encourage transport users to change travel behavior. – Support sharing experience and knowledge to enable better access to this information and help stakeholders to capitalize on these experiences and on relevant data and statistics. – Optimize urban mobility to encourage effective integration, interoperability and interconnection between different transport networks. – Improve road safety to achieve a high level of road safety, especially for vulnerable road users such as young people and the elderly. However only some plans have specific actions towards a real urbanmobility integration. For example the Perugia Mobility Plan define the “urban and mobility planning areas” where the land use changes and the new transport infrastructures are planned and implemented at the same time. The Bolzano Mobility Plan defines specific actions for the open spaces and pedestrian networks, that are considered as an integrated part of the multi-modal transport system. Another example is the Reggio Emilia Mobility Plan, that defines specific actions for the Transit Oriented Development of the metropolitan area. These innovative plans are the first examples of a new approach for the integrated transport and land use planning and represent the first step towards an effective integration towards new mobility patterns in cities and sustainable development of urban areas.